EVALUATION OF DAMAGE OF ROUNDWOOD ASSORTIMENTS CAUSED BY VARIED CONSTRUCTION, TECHNICAL SOLUTIONS AND CONDITIONS OF HARVESTER HEAD FEED ROLLERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The purpose of this study was to evaluate the depth of damages caused by harvester head feed roller spikes to birtch veneer logs, harvested according to top diameter group (18x25cm, 25<cm), spruce sawlogs (6x10cm), spruce and pine sawlogs according to top diameter group (10x14cm, 14x18cm). Thirteen technical solutions and conditions of the harvester head soft feed rollers (Moipu Standard, Rib), standard feed rollers (Multi-Tree Handling (MTH), Steel Thumbnail) and agreesive feed rollers (TP) were tested in this study.Regulation parameters of hydraulic system and angles of delimbing knife blades during the harvesting of stems in different woodland types and seasonality using single grip harvesters: John Deere 1270E, John Deere 1070E and John Deere 1070D equipped with harvester heads: H754; H480C and H460 were examined in clearcutting and thinning operations in twenty four wood felling sites in Kurzeme and Vidzeme region of Latvia.